Application of Parametrical Method Synthesis for Borehole Motors Design - Gečys, S.; Smolskas, P.; Žmuida, M. (Elektronika ir Elektrotechnika, 2010)
The design methodology of conventional induction motors is not suitable for the borehole motors due to specific and extraordinary operating conditions. The parametrical method synthesis for small power solid rotor and copper-cage solid rotor induction motors is developed, taking into account the specific operating peculiarities and limiting factors. The main construction coefficients and change limit related parameters of the equivalent circuit for the design of the borehole motors, applying the parametrical synthesis principles, are determined, considering the maximum transmitted active power through the supply circuit to the motor. The calculations of equivalent circuit parameters, characteristics, applying the proposed parametrical method synthesis and tests, are carried out. This confirms reliable operation in the concrete supply circuit.